Rainwater Harvesting with First Flush: Water Quality Analysis for Non-Potable Purpose - Sambas, Nurul Faradila (Universiti Teknologi PETRONAS, 2018)
The objectives of the research are to study the quality of rainwater harvested from a Rainwater Harvesting (RWH) system and also to evaluate the efficiency of the subsequent First Flush system. In order to divert poor quality of rainwater that may have a lot of impurities. The project also meant to identify the most suitable volume to flush away the contaminants in rainwater harvested before the rainwater collected from RWH system is safe to be used for non-potable purpose (i.e. irrigation, industry and toilet flushing). A RWH model were installed at an existing store building at Universiti Teknologi PETRONAS (UTP), Perak Darul Ridzuan. UTP is known as a green environment campus as it is located nearby to a large area of virgin forest that still unexplored by humans, thus the environment is engulfed with less air pollution.